Metabolomics Differences of the Donor Livers Between In Situ and Ex Situ Conditions During Ischemia-free Liver Transplantation. Issue 5 (22nd April 2023) - Guo, Zhiyong; Zhan, Liqiang; Gao, Ningxin; Zhang, Zhiheng; Huang, Shanzhou; Wang, Linhe; Zhu, Caihui; Jia, Zehua; Yin, Meixian; Li, Fangcong; Chen, Shirui; Luo, Tao; et al.
Abstract : Background: Ischemia-free liver transplantation (IFLT) has been innovated to avoid graft ischemia during organ procurement, preservation, and implantation. However, the metabolism activity of the donor livers between in the in situ and ex situ normothermic machine perfusion (NMP) conditions, and between standard criteria donor and extend criteria donor remains unknown. Methods: During IFLT, plasma samples were collected both at the portal vein and hepatic vein of the donor livers in situ during procurement and ex situ during NMP. An ultra-high performance liquid chromatography-mass spectrometry was conducted to investigate the common and distinct intraliver metabolite exchange. Results: Profound cysteine and methionine metabolism, and aminoacyl-tRNA biosynthesis were found in both in situ and ex situ conditions. However, obvious D-arginine and D-ornithine metabolism, arginine and proline metabolism were only found in the in situ condition. The suppressed activities of the urea cycle pathway during ex situ condition were confirmed in an RNA expression level. In addition, compared with extend criteria donor group, standard criteria donor group had more active intraliver metabolite exchange in metabonomics level. Furthermore, we found that the relative concentration of p-cresol, allocystathionine, L-prolyl-L-proline in the ex situ group was strongly correlated with peak alanine aminotransferase and aspartate aminotransferase at postoperative days 1–7. Conclusions: In the current study, we show the common and distinct metabolism activities during IFLT. These findings might provide insights on how to modify the design of NMP device, improve the perfusate components, and redefine the criteria of graft viability.